Phylogeny and biogeography of the Canarian Solanum vespertilio and S. lidii (Solanaceae) - Anderson, Gregory (2006)
The endemic and rare Solanum vespertilio and S. lidii from the Canary Islands are notable in being andromonoecious, self compatible, highly heterandrous (with short reward= anthers and one very long pollination= anther), and bearing strongly zygomorphic corollas. Solanum vespertilio flowers are also tetramerous, and some display enantiostyly. Given their island distribution, uncommon for solanums, and many distinctive reproductive features, the phylogenetic position is of interest. With new molecular data from the chloroplast trnT-F region and the nuclear granule-bound starch synthase gene (GBSSI or waxy), we confirm the hypothesis that these two species are phylogenetically associated with Solanum lineages from Africa, rather than with previously suggested Mexican species. The phylogeny facilitates understanding the evolution of the unique suite of reproductive characteristics in these island endemics.